2015
DOI: 10.1371/journal.pone.0137430
|View full text |Cite
|
Sign up to set email alerts
|

Noninvasive Multimodal Imaging to Predict Recovery of Locomotion after Extended Limb Ischemia

Abstract: Acute limb ischemia is a common cause of morbidity and mortality following trauma both in civilian centers and in combat related injuries. Rapid determination of tissue viability and surgical restoration of blood flow are desirable, but not always possible. We sought to characterize the response to increasing periods of hind limb ischemia in a porcine model such that we could define a period of critical ischemia (the point after which irreversible neuromuscular injury occurs), evaluate non-invasive methods for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
13
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(17 citation statements)
references
References 40 publications
4
13
0
Order By: Relevance
“…Furthermore, there was no significant variation in the maximum response times (p = 0.58, one-way ANOVA, n = 6), indicating that a comparable level of ischaemia was induced followed tourniquet application across all Pt-Pt configurations and animal species investigated. These findings corroborate recent work using noninvasive imaging in porcine limb that measured an immediate drop in oxygenated haemoglobin (within the first 10 min) after induction of ischaemia that continued to decrease over the course of the insult (3-4 h), albeit at a much slower rate [10]. Their objective was to measure locomotion recovery and required significantly longer durations of ischaemia to achieve this.…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…Furthermore, there was no significant variation in the maximum response times (p = 0.58, one-way ANOVA, n = 6), indicating that a comparable level of ischaemia was induced followed tourniquet application across all Pt-Pt configurations and animal species investigated. These findings corroborate recent work using noninvasive imaging in porcine limb that measured an immediate drop in oxygenated haemoglobin (within the first 10 min) after induction of ischaemia that continued to decrease over the course of the insult (3-4 h), albeit at a much slower rate [10]. Their objective was to measure locomotion recovery and required significantly longer durations of ischaemia to achieve this.…”
Section: Discussionsupporting
confidence: 87%
“…Compartment syndrome is a time-critical medical emergency, in which irreversible nerve and muscle damage can occur after just six hours of increased intra-compartmental pressure. Recovery from tissue ischaemia complications is largely dependent on tissue microcirculation [10] in the smallest blood vessels, including arterioles, capillaries, and venules, which are responsible for tissue oxygenation and, ultimately, tissue (and organ) health [11].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In previous studies, increases in R-B values indicated increased oxygenation of the wounds through more robust microvasculature. [ 14 16 ] This is likely secondary to the increases in angiogenesis in wounds that heal compared with those that dehisce. In this study, however, we had to explore more robust normalization techniques to exploit the small differences in the R-B values between healed and dehisced wounds.…”
Section: Discussionmentioning
confidence: 99%
“…Recent advances in image processing allow for the immediate assessment of tissue viability, something the authors believe beneficial when treating large, heterogeneous extremity wounds. In fact, previous studies utilized a 3CCD (three charge-coupled device) camera to evaluate changes in oxygenation in red blood cells[ 12 ], vessels[ 13 ], ischemic limbs[ 14 16 ], during pediatric appendectomies[ 17 ], and in partial and donor nephrectomies[ 18 , 19 ]. The present study seeks to ascertain the imaging characteristics of a heterogeneous population of extremity wounds prior to closure using a 3CCD camera, a commercially available and inexpensive device that records the levels of each of the three primary colors (red, green, and blue) to form a high-resolution image.…”
Section: Introductionmentioning
confidence: 99%